موقف الفقه الإسلامي من دفع الصدقات الإلزامية والتطوعية إلى الأقارب: دراسة فقهية مقارنة - الأكشة، جمال مهدي محمود (جامعة الأزهر - كلية الشريعة والقانون بتفهنا الأشراف - دقهلية, 2021)
يتكون هذا البحث من مقدمة، وتمهيد، وفصلين، وخاتمة، وفهارس عامة. وقد انتهيت في هذا البحث إلى ما يلي: 1- تطلق الصدقات الإلزامية ويراد بها زكاة الأموال والأبدان (الفطر)، وتتمثل الصدقات التطوعية فيما يتطوع به المسلم من أموال نقدية وعينية خارج نطاق الزكاة للفقير والمحتاج، ابتغاء مرضاة الله تعالى. 2- القرابة: صفة شرعية تثبت بسبب النسب ويترتب عليها آثار شرعية، وتتنوع باعتبار السبب الشرعي الذي نشأت من خلاله إلى أنواع ثلاثة: 1- قرابة النسب. 2- قرابة المصاهرة. ٣- قرابة الرضاع. 3- يجوز للمزكى أن يدفع زكاة ماله- بغير خلاف- وزكاة بدنه (الفطر)- على الراجح مما ذهب إليه جمهور الفقهاء- من سهم العاملين على الزكاة، والمؤلفة قلوبهم، وفي الرقاب، والغارمين، وفي سبيل الله، وابن السبيل، إلى الأقارب، بشرط أن يكونوا من أهل هذه الأسهم، وأيضا على أن نبدأ بالفقراء في زكاة الفطر ولا نتجاوزهم إلى غيرهم من مصارف الزكاة إلا لحاجة أو مصلحة. 4- لا يجوز للمزكي أن يدفع زكاة ماله وبدنه (الفطر) إلى والديه وأبنائه وبناته- بغير خلاف- ولا إلى أجداده وجداته وإن علوا، وأبناء أبنائه وبناته وإن نزلوا- على الراجح مما ذهب إليه الحنفية والشافعية والحنابلة- من سهم الفقراء والمساكين، إن كانوا من أهل هذين السهمين. 5- يجوز دفع زكاة الأموال والأبدان (الفطر) من سهم الفقراء والمساكين إلى الأقارب من غير الأصول والفروع، مثل الإخوة والأخوات، والأعمام والعمات، والأخوال والخالات، على الراجح مما ذهب إليه جمهور الفقهاء. 6- اتفق الفقهاء على أنه لا يجوز للزوج أن يدفع زكاة ماله وبدنه (الفطر) إلى زوجته، ولكن يجوز للزوجة أن تدفع زكاة مالها وبدنها (الفطر) إلى زوجها من سهم الفقراء والمساكين، إذا كان من أهل هذين السهمين، وذلك على الراجح مما ذهب إليه أبو يوسف ومحمد من الحنفية، ومالك في رواية، والشافعية، والحنابلة في رواية، والثوري ابن المنذر وأبو عبيد. 7- إذا كانت صدقة التطوع مستحبة فإن دفعها إلى الأقارب المحتاجين أكثر استحبابا، وإذا تساوى الأقارب في الحاجة قدم الأقرب فالأقرب. 8- دفع صدقة التطوع إلى القريب ذي العداوة أفضل من دفعها إلى غيره من الأقارب. 9- يستحب تقديم العالم وصاحب الدين وذي العائلة من الأقارب على غيرهم عند إعطاء صدقة التطوع.
This research consists of an introduction, a boot, two chapters, a conclusion, and general indexes. In this research, I have concluded: (1) Mandatory handouts are released and zakat is intended for money and acres (mushrooms), and voluntary handouts are the cash and in-kind that a Muslim volunteers outside the scope of zakat for the poor and needy, for the sake of his patients. (2) Kinship: a legitimate status established by descent with legitimate implications, and varied by consideration of the legitimate cause through which it originated into three types: 1- Approximately the proportions. 2- Nearly the smelter. 3- Near breastfeeding. (3) It is permissible for a zakat to pay his money, not otherwise, and to his body (mushrooms)- more likely than the opinion sought by the audience of jurists – from the shares of zakat workers, the author of their hearts, in necks, garmin, for the sake of God, and ibn al-Sabil, to relatives, provided that they are the people of these shares, and also to start with the poor in zakat of mushrooms and not exceed them to other zakat banks except for need or interest. (4) Al-Zaki may not pay zakat of his money and his body (mushrooms) to his parents, sons and daughters, without dispute, nor to his grandparents and grandmothers, even if they are high, and if they go down, on the most likely way, from what hanafi, Shafi'I and Hanbala went to, from the shares of the poor and the poor, if they are the people of these shares. (5) Zakat may be paid from the shares of the poor and poor to relatives without assets and branches, such as brothers and sisters, uncles, aunts, uncles, brothers and aunts, most likely from the audience of jurists. (6) The jurists agreed that the husband may not pay zakat of his money and his body (mushrooms) to his wife, but the wife may pay zakat of her money and her body (mushrooms) to her husband from the shares of the poor and the poor, if he is one of the people of these shares, most likely from what Abu Yusuf and Mohammed went to from Hanafia, Malik in a novel, Shafi'a, Hanbala in a novel, and the revolutionary Ibn al-Munther and Abu Obeid. (7) If the charity of volunteering is desirable, its payment to needy relatives is more desirable, and the relatives are equally in need, the nearest and closest. (8) Paying the volunteer handout to the hostile relative is better than paying it to other relatives. (9) It is desirable to offer the world, the religious owner and the family relatives over others when giving the charity of volunteering.
Keywords: الفقه الإسلامي -- المذاهب الإسلامية -- العبادات الدينية -- زكاة الأموال